ANALISIS PENGGUNAAN SOSIAL MEDIA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI SEKOLAH DASAR - Siswoyo, Andika Adinanda; Pratama Roda’i, Nur Indah Putri Ayu; Ramadhani, Nadia; Zaini, Moh. (CV. Jendela Gagasan, 2024)
This study aims to analyze the impact of social media use on the character development of students at SDN Bunder 1, Pademawu District, Pamekasan Regency. Using a descriptive qualitative approach, the study involved 26 sixth-grade students as informants. With the rise of social media platforms such as TikTok, YouTube, and Instagram, concerns have emerged regarding their effects on children's behavior and personality. Through qualitative research methods, this study seeks to examine how social media influences students' social interactions and character formation. The findings show that all students use social media, with TikTok being the most popular platform. Social media provides benefits in learning, with students reporting positive effects such as increased self-confidence and ease in making friends. However, challenges also arise as students may imitate negative behaviors they encounter on social media. Therefore, the role of parents and teachers is crucial in supervising and guiding children's use of social media.